2019
DOI: 10.1186/s13068-018-1345-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an essential regulator controlling the production of raw-starch-digesting glucoamylase in Penicillium oxalicum

Abstract: BackgroundRaw-starch-digesting glucoamylases (RSDGs) from filamentous fungi have great commercial values in starch processing; however, the regulatory mechanisms associated with their production in filamentous fungi remain unknown. Penicillium oxalicum HP7-1 isolated by our laboratory secretes RSDG with suitable properties but at low production levels. Here, we screened and identified novel regulators of RSDG gene expression in P. oxalicum through transcriptional profiling and genetic analyses.ResultsPenicilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…In N. crassa, the female fertility-7 (FF-7) is required for initiation of sexual development, and ff-7 mutant does not produce protoperithecia and perithecia as well as ascospores (Carrillo et al, 2017). In P. oxalicum HP7-1, it was demonstrated that POX09752, ortholog of PDE_06843 in P. oxalicum 114-2, is involved in the regulation of raw-starchdigesting enzymes (Zhang et al, 2019). This is consistent with the inferred regulatory interactions where PDE_06843 regulates one α-amylase encoding gene PDE_04683 (GH13-5) in P. oxalicum; and PECH_007045 regulates two α-amylase encoding genes PECH_000987 (GH13-5) and PECH_000986 (GH13-1) in P. echinulatum.…”
Section: Mining the Regulatory Networkmentioning
confidence: 99%
“…In N. crassa, the female fertility-7 (FF-7) is required for initiation of sexual development, and ff-7 mutant does not produce protoperithecia and perithecia as well as ascospores (Carrillo et al, 2017). In P. oxalicum HP7-1, it was demonstrated that POX09752, ortholog of PDE_06843 in P. oxalicum 114-2, is involved in the regulation of raw-starchdigesting enzymes (Zhang et al, 2019). This is consistent with the inferred regulatory interactions where PDE_06843 regulates one α-amylase encoding gene PDE_04683 (GH13-5) in P. oxalicum; and PECH_007045 regulates two α-amylase encoding genes PECH_000987 (GH13-5) and PECH_000986 (GH13-1) in P. echinulatum.…”
Section: Mining the Regulatory Networkmentioning
confidence: 99%
“…Generally, glycoside hydrolases expression is regulated by upstream transcription factor(s) in filamentous fungi [ 16 , 21 , 22 ]. Comparative analysis of significantly changed genes in all three strains revealed 40 DEGs encoding putative transcription factors (TFs) (Additional file 8: Table S8), most of which contained zinc-related structures (Zn_clus, GATA, Zn2Cys6, bZIP, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the dramatic increase in the transcription levels of amy15A benefited from not only the absence of the repressor CreA but also the increase in the activator AmyR. In view of this conclusion, it is desirable to further improve the efficiency of amy15A(p) by overexpressing AmyR or other potential activitors when inhibition effect mediated by CreA is relieved [22]. In addition, the negative regulation of CreA on hyphal growth and enhanced secretion of Amy15A in liquid indicate that Δ13A-OamyR-ΔCreA has higher expression efficiency per unit biomass, which would benefit protein productivity in high-density fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant-biomass-degrading enzymes activities, including SSDE, raw starch-digesting enzymes (RSDE), cellulase and xylanase activities, were assayed as previously described Zhang et al, 2019). Briefly, 50 µL of appropriately diluted crude extract produced from the parental strain TpKu70 or its deletion mutant TP05746, were added to 450 µL of 100 mM citrate-phosphate buffer (pH 5.0) containing 1% SCS (Sigma-Aldrich), 1% raw cassava flour (farmer's market, Nanning, China), 1% CMC-Na (Sigma-Aldrich, Darmstadt, Germany), or 1% beechwood xylan (Megazyme International Ireland, Bray, Ireland), and 1 mL of 100 mM citrate-phosphate buffer pH 5.0, containing Whatman No.…”
Section: Measurement Of Pbde Production and Intracellular Protein Conmentioning
confidence: 99%